HOUSEHOLDS’ WILLINGNESS TO PAY FOR IMPROVED DRINKING WATER- A CASE STUDY ON KHULNA CITY CORPORATION USING DISCRETE CHOICE MODEL - Akram, Wasim; Alam, Md Touhidul (PEOPLE: International Journal of Social Sciences, 2019)
The purpose of the study is to find out the willingness to pay for improved drinking water services using Discrete Choice Model (DCM). To carry out the study, concept profiling has been done and data have been collected randomly from 120 households from two areas, Basupara and Najirghat of Ward-26 of KCC. Multinomial Logit Model (MLM) has been taken to into consideration to see relative willingness to pay (WTP) for accessing improved drinking water services being in status quo position. The study explores that, people who have the willingness to pay BDT 450 are 9.67 times higher than the willingness to pay BDT 250. On the other hand, people who have the willingness to pay BDT 600 are about 2.38 times more likely to choose Alternative-2 option than those who have the willingness to pay BDT 250.